Advanced technology for human support in space (National Academy Press, 1997)
This report was prepared in response to a NASA request to the National Research Council (NRC) to examine, evaluate, and make recommendations regarding the four research areas that make up NASA's Advanced Human Support Technology Program. These research areas provide technologies for advanced life support systems, environmental monitoring and control, extravehicular activities, and space human factors engineering. The four research areas are briefly described in this report and general findings and recommendations of the NRC Committee on Advanced Technology for Human Support in Space follow.